Defining SARS-CoV-2 breakthrough infection needing hospitalization in mass vaccination era: from disease-centered to patient-centered care: SARS-CoV-2 breakthrough infection in hospital care - Ticinesi, Andrea; Nouvenne, Antonio; Parise, Alberto; Prati, Beatrice; Meschi, Tiziana (Acta Biomedica Atenei Parmensis, 2022)
After the implementation of mass vaccination campaigns, breakthrough infections by SARS-CoV-2 are being increasingly observed worldwide, due to high pervasiveness of viral spread, emergence of novel variants, progressive ease of restrictive measures and waning protection against infection. Although breakthrough infections have generally lower clinical severity than COVID-19 in unvaccinated subjects, a consistent number of patients may still require hospitalization. These patients are generally old, frail and with a high number of comorbidities. Despite COVID-19-related symptoms are generally milder, they may still exhibit complicated clinical course for their intrinsic clinical complexity. The organization of hospital care should thus consider the changing epidemiology of patients admitted with SARS-CoV-2 infection in the post-vaccine era, to improve the quality and appropriateness of care.